Governança global e redes globais de políticas públicas: atores brasileiros no cenário das mudanças climáticas - Sette, Ana Tarsila de Miranda e Souza (2010)
Based on sustainable development and climate change mitigation, public policies are being developed to reverse the growing degradation of natural ecosystems, enabling new forms of cooperation in the global interface. The recent trends indicate that global governance has changed the focus of activities among governments for the multi-sectoral initiatives, governance at the international level for governance at various levels and a formal and legalistic approach to a more informal, participatory and integrated. In this context, the global networks of public policy arise as a possible component of this new governance structure. The Brazilian players are increasingly joining the global network of public policies aimed at reducing climate change with its plans and policies for clean development, indicating that the structural and relational models such as this can be considered as viable instruments of global governance when it comes to minimizing the environmental risks that threaten the planet. Therefore, the objective of the study was to verify the institutionalization of the global network of public policies directed at mitigation of climate change among Brazilian actors related policies of reducing or offsetting emissions of greenhouse gases. For this, was conducted a survey of literature on the subject of study and empirical research with the actors of the Brazilian public sector, private sector and nongovernmental organizations involved in the network of global public policy. The results showed that the factors analyzed in order to verify the institutionalization of the network between the Brazilian actors, only some of them pointed to this institutionalization. It was noted an attempt to institutionalize the network, however, much remains to be developed for a full institutionalization.